Case Report: Composite Angioimmunoblastic T-Cell Lymphoma and Epstein-Barr Virus-Positive B-Cell Lymphoproliferative Disorder as Other Iatrogenic Immunodeficiency-Associated Lymphoproliferative Disorders - Kakiuchi, Seiji; Yakushijin, Kimikazu; Takagi, Ikumi; Rikitake, Junpei; Akiyama, Hiroaki; Matsuba, Hiroyuki; Hayashi, Yoshitake; Kajimoto, Kazuyoshi; Iwata, Nobuko (Frontiers in Medicine, 2020)
Immunosuppressants are widely used to treat patients with rheumatoid arthritis (RA), and their adverse effects have been known to cause other iatrogenic immunodeficiency-associated lymphoproliferative disorders (OIIA-LPDs). We report a patient with RA who had been treated with methotrexate (MTX) and tacrolimus (TAC) and who developed whole body lymphadenopathy. We simultaneously confirmed angioimmunoblastic T-cell lymphoma (AITL) through a right cervical lymph node biopsy and Epstein-Barr virus-positive B-cell lymphoproliferative disorder (EBV-positive B-LPD) through a bone marrow examination. After cessation of immunosuppressant therapy, both lymphomas completely disappeared. Patients with AITL are occasionally reported to develop B-cell lymphoma through reactivation of the EBV, which leads to clonal expansion in the microenvironment. Immunohistochemistry results revealed that both lymphoma components were positive for EBV-encoded RNA. Moreover, in this patient, the plasma EBV DNA level was found to be high; therefore, EBV infection was a probable etiology. Synchronous coexistence of AITL and B-LPD as an OIIA-LPD has rarely been reported. This case report is the first to discuss the disappearance of both lymphomas on withdrawal of immunosuppressants only. AITL occasionally accompany B-LPD; however, this composite lymphoma comprised AITL and B-LPD, and OIIA-LPDs should not be overlooked.